The Effect Of Insider Ownership, Dept Policy, Divident Payment Policy And Profitability On Stock Return (On The Manufacture Companies Registered in BEI) - ALdo Hermanda Prasma Putra; Akhmad Darmawan (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2014)
This research aimed to find out the effect of insider ownership. debt policy, dividen payment policy and profitability partially and simulianeusly on stock return on the manufacture companies registered in BEI in 2010-2012 The data of this research was from audited financial report and annualy financial report gained from www.idx.co.id. The sample of this research was the manufacture companies registered in BEI in 2010-2012. The analysis technicue was by double linier regression. The result of this research showed that simultaneusly, insider ownership, debt policy and dividend payment policy efectted significantly on stock return. Partially, only 1 independent variable that was profitability that effected positively significant to the stock return, while insider ownership had a negative significant effect, and partially, debt policy and dividen payment did not affect on stock return. the researcher suggested that the investor of insider ownership variable and profitability could be applied to explain stock return of the maufacture companies then this ratio could be the investor's consideration in analyzing the company's performance that influance the stock return rise Keyword : Insider Ownership, Dept Policy, Dividen Payment Policy, Prifitability Stock Return